In infectious diseases, Echinacea comes to the rescue - Mahira Amirova; Mahbuba Nabi Valiyeva (Annals of Systems Biology - Peertechz Publications, 2022)
E. purpurea has amazing medicinal properties that effectively deal with human diseases. Today, we find frightening figures in the WHO news about the increase in coronavirus infection and the number of deaths. This article presents a simple way of self-defense by increasing the body's immune reactivity. In order to alleviate the condition and prevent not only COVID but also a variety of viral, as well as bacterial, and fungal infections, doctors can use the ornamental plant Echinacea (E.), which was once used by the indigenous people of America, the Indians, for almost all occasions. This article presents a small list of important biologically active components of E. and the range of their use, as well as a simple recipe for making a healing solution.